Gut Bacterial Metabolite Urolithin A (UA) Mitigates Ca2+ Entry in T Cells by Regulating miR-10a-5p - Zhang, Shaqiu; Al-Maghout, Tamer; Cao, Hang; Pelzl, Lisann; Salker, Madhuri S.; Veldhoen, Marc; Cheng, Anchun; Lang, Florian; Singh, Yogesh (Frontiers in Immunology, 2019)
The gut microbiota influences several biological functions including immune responses. Inflammatory bowel disease is favourably influenced by consumption of several dietary natural plant products such as pomegranate, walnuts and berries containing polyphenolic compounds such as ellagitannins and ellagic acid. The gut microbiota metabolises ellagic acid resulting in the formation of bioactive urolithins A, B, C and D. Urolithin A (UA) is the most active and effective gut metabolite and acts as a potent anti-inflammatory and anti-oxidant agent. However, whether gut metabolite UA, affects the function of immune cells remains incompletely understood. T cell proliferation is stimulated by store operated Ca2+ entry (SOCE) resulting from stimulation of Orai1 by STIM1/STIM2. We show here that treatment of murine CD4+ T cells with UA (10 µM, 3 days) significantly blunted SOCE in CD4+ T cells, an effect paralleled by significant downregulation of Orai1 and STIM1/2 transcript levels and protein abundance. UA treatment further increased miR-10a-5p abundance in CD4+ T cells in a dose dependent fashion. Overexpression of miR-10a-5p significantly decreased STIM1/2 and Orai1 mRNA and protein levels as well as SOCE in CD4+ T cells. UA further decreased CD4+ T cell proliferation. Thus, the gut bacterial metabolite UA increases miR-10a-5p levels thereby regulating Orai1/STIM1/STIM2 expression, store operated Ca2+ entry and proliferation of murine CD4+ T cells.